Theatre Royal, Drury-Lane, Wednesday, March 31,1819, a grand selection of ancient & modern music - Theatre Royal, Drury Lane (London, England):::Creator:::::::::::: (Theatre Royal ; Rodwell, printer; London, 2020)
Handbill listing works to be performed at the Theatre Royal on March 30, 1814, with names of performers, including Beethoven's Wellington's Victory, op. 91 and the Kyrie from his Mass in C, op. 86.